2022
DOI: 10.3390/jcm11123353
|View full text |Cite
|
Sign up to set email alerts
|

Mental Stress and Cardiovascular Health—Part I

Abstract: Epidemiological studies have shown that a substantial proportion of acute coronary events occur in individuals who lack the traditional high-risk cardiovascular (CV) profile. Mental stress is an emerging risk and prognostic factor for coronary artery disease and stroke, independently of conventional risk factors. It is associated with an increased rate of CV events. Acute mental stress may develop as a result of anger, fear, or job strain, as well as consequence of earthquakes or hurricanes. Chronic stress may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 184 publications
1
36
0
4
Order By: Relevance
“…[ 2 ] The sympathetic response, more commonly known as the fight or flight response, may potentially play a role in the development of myocardial ischemia. [ 3 ] A similar mechanism has also been suggested to increase ischemic stroke. [ 4 ] There is also a unique difference in myocardial ischemia caused by mental stress as compared with physical exercise.…”
mentioning
confidence: 89%
“…[ 2 ] The sympathetic response, more commonly known as the fight or flight response, may potentially play a role in the development of myocardial ischemia. [ 3 ] A similar mechanism has also been suggested to increase ischemic stroke. [ 4 ] There is also a unique difference in myocardial ischemia caused by mental stress as compared with physical exercise.…”
mentioning
confidence: 89%
“…Treatment of major depression even in individuals without baseline CAD substantially reduced the development of coronary events [ 156 ]. In a small-size study of patients with stable CAD and MSIMI (see Part I [ 5 ]), treatment with escitalopram reduced the rate of MSIMI demonstrated on echocardiography and/or ECG, probably due to a beneficial effect on platelets aggregation [ 157 ]. However, other studies showed little or no evidence that treating depression in such patients improves CV outcomes [ 158 , 159 ].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Epidemiological studies suggest that acute and chronic mental stress, such as anger, fear, job strain, depression or exposure to natural disasters, may contribute to the pathogenesis and development of coronary artery disease (CAD) [ 1 , 2 , 3 , 4 ]. The first part of the review on the relationship between psychological stress and cardiovascular (CV) disease focused on the brain response to negative emotions and autonomic nervous system imbalance, leading to hemodynamic and coronary artery responses to mental stress [ 5 ]. The aim of Part II is to review the evidence for the clinical association between mental stress and systemic CV effects, including endothelial dysfunction, inflammation, hypertension, arrhythmia, and stress cardiomyopathy, based on most recent literature findings.…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure is observed in as many as seven out of ten people with a first heart attack and eight out of ten people with a first stroke. In addition, excessive sodium intake and excessively high serum LDL lipoprotein levels are also identified as risk factors [1,[6][7][8]. Although some risk factors are not firmly established in the scientific evidence, they are still considered to be among the main ones.…”
Section: Introductionmentioning
confidence: 99%